The Process of Creating Buddhist and Social Values of Novices With 9 Grades of Pali Studies - Srivichai, Suddhipong (Arts of Management Journal, 2023)
The objectives of the research article were: 1) to study factors leading novices to succeed in the 9th grade examination of Pali Studies; 2) to study the process of creating Buddhist and social values; and 3) to propose the process of creating Buddhist and social values. The study employed multiphase mixed methods. At first, the qualitative research method was used, and its data were collected by in-depth interviews with 15 experts and then analyzed by the inductive method. In the second process, the data were collected through group discussions with nine experts and analyzed by the inductive method. After that, the quantitative research method was applied. The data were collected from 30 samples and analyzed by percentage, mean, and standard deviation. The results of the study showed that: 1. The factors leading novices to succeed in the 9th grade examination of Pali studies were that those novices had taught Dhamma and Pali to others, arranged the significance of their burdens, demonstrated effort and tolerance in the study, and had their Buddhist works published. 2. The process of creating Buddhist and social values in the novices who have completed the 9th grade examination of Pali Studies comes from friendships with family members, Iddhipada principles, ability in integration of Buddhism and modern sciences, love of reading, self-training, listening to others’ opinions, and self-inspiration. 3. The proposed processes of creating Buddhist and social values by the novices who have completed the 9th grade examination of Pali Studies are as follows: principles of Kalyanamitta and Iddhipada, incentive and inspiration, online publication of works integrated with theory and practice, creative thinking integrated with belief, team-working, and life-long learning.